Physico-Chemical Properties Of Sponge Cake Made From Wheat Flour Incorporated With Mango (Mangifera Indica Var. Chokanan) Pulp And Peel Flour - Wong, Lee Min (2012)

(untitled)
The objective of this research was to determine the physico-chemical, nutritional and organoleptic attributes of sponge cake by partial substitution of wheat flour with mango pulp and peel flour (MPuF and MPeF, respectively) at different levels (control, 5, 10, 20 and 30%). In the present study, the chemical composition, antioxidants and functional properties of MPuF and MPeF were evaluated. Compared to the commercial wheat flour (WF), the MPuF and MPeF were significantly (p<0.05) low in moisture and protein, but high in crude fibre and ash content. The MPuF and MPeF showed a balance in soluble and insoluble dietary fibre (SDF and IDF) proportions, ranging from 29 to 35% and 65 to 70% of total dietary fibre (TDF) content, respectively.